2000
DOI: 10.1590/s0066-782x2000000200008
|View full text |Cite
|
Sign up to set email alerts
|

Coarctation of the aorta corrected during childhood. Clinical aspects during follow-up

Abstract: Maia et al Coarctation of the aorta corrected during childhood Arq Bras Cardiol volume 74, (nº 2), 2000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…The results of this study show that reduced proximal COA compliance interacts with COA and amplified P K dP. This could in part explain why some patients who have had a good repair of COA may have residual upper body hypertension at rest or with exercise despite having little evidence of significant recoarctation (Nanton and Olley, 1976; Maia et al, 2000; Gunthard et al, 1996). …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The results of this study show that reduced proximal COA compliance interacts with COA and amplified P K dP. This could in part explain why some patients who have had a good repair of COA may have residual upper body hypertension at rest or with exercise despite having little evidence of significant recoarctation (Nanton and Olley, 1976; Maia et al, 2000; Gunthard et al, 1996). …”
Section: Discussionmentioning
confidence: 72%
“…Patients with COA have higher incidence of systemic hypertension (up to 68%) even after successful repair of the COA (Clarkson et al, 1983; Maia et al, 2000). Systemic hypertension is associated with elevated systemic resistance and reduced systemic compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Despite a satisfactory reduction in BP soon after operation, studies with longer follow-up have demonstrated that approximately one-third of patients develop late hypertension, even when surgery is performed in the neonatal period. 15,16,17 Clarkson and colleagues 18 showed that the prevalence of late hypertension increased with the duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Correct diagnosis is very important because blood pressure tends to normalize after correction of the aortic defect 10 . In turn, bicuspid aortic valve is the most common cardiac malformation, which may be traditionally associated with coarctation of the aortic arch, but also several other malformations 11 .…”
Section: Commentsmentioning
confidence: 99%